Do Kenyan University STEM Graduates Possess Employable Skills for the Job Market? - Kiweu, Josephat M.; Mulwa, David; Kinyili, Jacinta; Muriungi, Pamela; Kimiti, Richard; Muola, James (European Journal of Education Studies, 2021)
Economic growth world over is based on the supply and availability of Science, Technology, Engineering and Mathematics graduates due to their desired skills. However, a major concern in most developing countries including Kenya is whether STEM graduates possess the skills required by labour market. This study therefore seeks to find out if there exists a ‘skills gap problem’ in STEM graduates emerging from Kenyan Universities. The study adopted a descriptive survey research design. The sample size of the study were 66 lecturers, 59 laboratory technologists and 275 students in the STEM disciplines in the four technology-baseduniversities in Kenya. A purposive sample of four employers where most STEM graduates seek internshipwere used to seek employer views on competency of the graduates. Data was collected through five sets of questionnaires for each for lecturers, laboratory technologists, employers, alumni and students. Analysis of data was done through the use of descriptive and inferential statistics. The findings suggest that STEM graduates coming out from Kenyan universities don’t receive enough training thus requiring more exposure on practical sessions to be productive and more mentoring. Training based on STEM curriculum was relevant for the Kenyan industries despite the study indicating that there are inadequacies with the STEM training facilities.The study also revealed that the staff handling the students are competent, and theoretical and practical lessons are adequately prepared.
Keywords: science, technology; engineering and mathematics; Kenyan universities